PENDIDIKAN 4.0: PERANAN TRANSFER PENGETAHUAN DALAM PENINGKATAN BISNIS DI KABUPATEN BENGKAYANG, DAERAH PERBATASAN - Vasantan, Priska (JURNAL BORNEO AKCAYA, 2020)
The purpose of this study was to describe the role of knowledge transfer in the education that can improve business in Bengkayang Regency. Information management is one of the things that must be faced by disadvantaged areas, especially in industrial revolution 4.0. Bengkayang Regency is one of the areas directly adjacent to Malaysia so that there are many cross-border businesses. In the era of this industrial revolution, the government has a 4.0 making Indonesia program, namely making Indonesia becomes the 10th largest economist in the world. One of the factors to improve is the quality of human resources. However, the quality of human resources in Bengkayang Regency was is very low due to the poor education quality. This research was conducted using a phenomenological qualitative method with observation and in-depth interviews. The informants were elementary school students studying in Year 4, 5, 6. They studied in the village of Tampe and 4 students in Shanti Bhuana (ISB) institute located in Bengkayang. The results showed that the quality of human resources was strongly influenced by the quality of education and the quality of education was strongly influenced by the knowledge transfer process implemented in schools